MENA Export Performance and Specialization : The Role of Financial Sector Development and Governance - Wood, Christina A.; Yang, Judy (World Bank, Washington, DC, 2016)
Industry and financial profiles of MENA firms may underpin the observation that MENA country exports are below potential and skewed toward low value-added goods that are unable to spur rapid job creation and inclusive growth. To assess this link, the paper combines analysis highlighting external financing as a determinant of export performance, and analysis highlighting sector asset tangibility and governance. Why? Because high value-added sectors tend to have higher shares of intangible assets and to create innovative products requiring substantial research and development or investments, thereby making these sectors more dependent on external financing. Using sector- and firm-level export data with country-level indicators, the results indicate that countries with more developed financial sectors and stronger governance tend to have higher exports from sectors that are more reliant on finance external to the firm, and lower exports from sectors with higher shares of tangible assets. Interestingly, financial sector development boosts exports less in MENA than in non-MENA countries. To foster expansion of higher value exports, the results suggest a critical need for: (i) deeper financial sector development that strengthens market-based systems, such as asset registries and credit reporting agencies, and (ii) strengthening of legal and governance frameworks.